ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK UMUM SYARIAH SEBELUM DAN SESUDAH TERDAMPAK COVID-19 (Jurnal Proaksi, 2022)
AbstractThe development of Islamic Banks is currently growing rapidly, but the Covid 19 Pandemic has had an impact on the world's economy, especially in Indonesia. One of the affected sectors is the banking industry. The purpose of this study was to analyze the differences in the performance of Islamic banks before and during the Covid-19 pandemic. The Islamic banks studied in this study are Islamic banks registered with the Otoritas Jasa Keuangan and Bursa Efek Indonesia. The variables of financial performance is based on the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method determined by Bank Indonesia. This study uses  the Paired Sample t-test analysis method. The total sample of  11 Islamic banks. The results of this study indicate that based on the ratio of NPF,ROA and GCG there is no difference in the level of health before and after the covid-19 pandemic, while based on the ratio of CAR there is a difference in the level of health before and after the COVID-19 pandemic.Keywords: Bank Soundness Level, RGEC